ANALISIS ASUHAN KEPERAWATAN DENGAN INTERVENSI INOVASI SWEDISH MASSAGE PADA PASIEN HIPERTENSI YANG MENGALAMI KECEMASAN DI RT 001/RW 013 KELURAHAN BOJONGGEDE, BOGOR - Natasya Dwiyustiani, (2022)
The prevalence rate of anxiety disorders increased by 40% to 47% in the elderly. From the data, the prevalence rate of anxiety disorders was higher in the elderly. Hypertension which is commonly suffered by the elderly can be a trigger for anxiety. Similarly, the factors that cause blood pressure to increase, one of which is anxiety. Complementary therapy Swedish massage is a massage therapy that has benefits for reducing anxiety and lowering blood pressure. The purpose of this study was to determine whether the Swedish massage therapy innovation intervention had an effect on overcoming anxiety in elderly patients with hypertension at Rt 001 Rw 13, Bojonggede Village, Bojonggede District, Bogor. This analysis uses 2 samples of respondents, 1 respondent managed and 1 respondent resume. At the beginning of the study, both patients had scores from the Zung Self-rating Anxiety Scale (SAS/ZSRAS) questionnaire, which was 48 for patients being managed and 50 for resume patients who were included in the mild anxiety category. The results showed that both patients who were given the intervention had a score decreased to 40 in managed patients and 44 in resume patients, which means that their anxiety decreased and could be categorized as non-existent anxiety. Keywords: Hypertension, Anxiety in Hypertension, Swedish Massage